2011
DOI: 10.2135/cropsci2010.06.0335
|View full text |Cite
|
Sign up to set email alerts
|

Allele Mining of Exotic Maize Germplasm to Enhance Macular Carotenoids

Abstract: Lutein and zeaxanthin are commonly referred to as the macular carotenoids, as they are localized to ocular tissues and their loss is associated with age-related macular degeneration. Thirty-four high-carotenoid (HiC) lines exhibiting uniquely high concentrations of carotenoids resulted from alíele mining of the Orange Flint race using traditional breeding techniques and visual selection for deep orange endosperm color. Total carotenoid concentrations of the HiC lines ranged from 50 to 101 pg g"^ dry weight (DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 59 publications
4
53
1
1
Order By: Relevance
“…Extensive studies were conducted to characterize concentrations of carotenoids in diverse tropical and temperate maize germplasm and found considerable natural genetic variations in accumulation of provitamin A and other carotenoids (Blessin et al 1963;Kurilich and Juvik 1999;Egesel et al 2003;Berardo et al 2004;Islam et al 2004;Chander et al 2008;Vallabhaneni and Wurtzel 2009;Burt et al 2011;Muthusamy et al 2015). To assess the extent of variation in carotenoid composition and content in adapted germplasm available for breeding, we also evaluated 421 tropical-adapted yellow to orange endosperm maize inbred lines in several independent trials (Menkir et al 2008).…”
Section: Genetic Potential For Provitamin a Enrichment In Maizementioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies were conducted to characterize concentrations of carotenoids in diverse tropical and temperate maize germplasm and found considerable natural genetic variations in accumulation of provitamin A and other carotenoids (Blessin et al 1963;Kurilich and Juvik 1999;Egesel et al 2003;Berardo et al 2004;Islam et al 2004;Chander et al 2008;Vallabhaneni and Wurtzel 2009;Burt et al 2011;Muthusamy et al 2015). To assess the extent of variation in carotenoid composition and content in adapted germplasm available for breeding, we also evaluated 421 tropical-adapted yellow to orange endosperm maize inbred lines in several independent trials (Menkir et al 2008).…”
Section: Genetic Potential For Provitamin a Enrichment In Maizementioning
confidence: 99%
“…Perhaps the formation of broad-based synthetics from tropicaladapted maize inbred lines displaying different carotenoid composition and content that also contain diverse exotic germplasm in their genome and subjecting them to recurrent selection can be a viable strategy to increase accumulation of favorable alleles of the different genes in the populations. Additional infusion of orange flint germplasm from Argentina and other countries with known potential to contribute high levels of zeaxanthin and lutein (Burt et al 2011) into these broad-based synthetics can further diversity and expand their genetic base and increase the probability of generating lines combining carotenes and xanthophylls to much higher levels. During each selection cycle, visual assessment for desirable kernel properties and agronomic features coupled with screening for favorable allele-specific markers of LcyE, CrtRB1 and other genes (Harjes et al 2008;Yan et al 2010;Wurtzel et al 2012;Owens et al 2014) may allow efficient selection of progenies with combination of alleles of these genes for recombination to further improve the populations.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Five yellow dent inbred maize lines (A632, A619, CG33, CG60, and CG102); two white inbred lines (cgx333 and SD80); and 13 high-carotenoid inbred lines (HiC2,HiC3,HiC7,HiC8,HiC9,HiC16,HiC17,HiC21,HiC23,HiC24,HiC25,HiC26,and HiC31) (Burt et al 2011) were used in this study. A632 and CG60 were chosen as they both exhibit carotenoid profiles that are higher in zeaxanthin relative to lutein (Burt et al 2011).…”
Section: Inbred Lines and Hybridsmentioning
confidence: 99%
“…For instance, the p1 gene, encoding a Myb-like transcription factor, can account for 35%-60% of the total phenotypic variation for maysin concentrations, depending on the particular mapping population (McMullen et al 1998). Work on the carotenoid pathway (Burt et al 2011) showed that effective allele mining from exotic populations using simple visual selection for deep orange endosperm colour could achieve very high carotenoid levels and different carotenoid profiles that could not be adequately explained by the diagnostic polymorphisms suggested by Harjes et al (2008) or Yan et al (2010). This suggests that there is, at least in some populations, potential for drastic improvement of carotenoid content and profile involving loci other than LcyE or CrtRB1.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in dietary carotenoids comes from their precursors of vitamin A, antioxidant properties and the association between carotenoid deficiencies and many chronic human diseases (Burt et al, 2011(Burt et al, , 2013. Breeding to increase β-carotene levels in cereal grains, termed provitamin A biofortification, is an economical approach to address dietary vitamin A deficiency in the developing world (Dwens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%